Enhancement of electroactive phases in free-standing, flexible thin films of PVDF with addition of p-block chlorides. (9th January 2020) - Thakur, Abhishek; Dam, Siddhartha; Nath, Deena; Chandra Shekar, N.V.; Amarendra, G.; Hussain, Shamima
Abstract: Facile formation and enhancement of electroactive (EA) phases contributing to piezo-properties, using metal salt additives in free-standing flexible thin films of Polyvinylidene fluoride (PVDF) synthesized using sol-gel method with minimum resources has been reported. Enhancement in the EA phases, with the metal salt additives were studied using X-ray diffraction (XRD). Well oriented spherulites were observed in the pristine samples. A drastic change in morphology for samples with salt additives was observed. The presence of salts were confirmed using Energy dispersive X-ray spectroscopy (EDS). Confirmation of phases and their quantification was done using Raman and Infra-red spectroscopy, respectively. Raman and Infra-red spectroscopies, showed increment in the EA phases with the addition of metal halides. Possible rearrangement of polymer chains due to metal salt additives has been discussed. Graphical abstract: Image 1 Highlights: Enhancement of electroactive (EA) phases in free-standing flexible thin films using sol-gel method with minimum resources. Confirmation of phases present and their quantification using Raman and Infra-red spectroscopy. Significant increment in the EA phases with the addition of metal halides. Possible rearrangement of polymer chains due to metal salt additives has been discussed.